WELCOMING INDUSTRY 4.0 COMPETITION WITH SPEED UP IT DIGITIZATION : STORIES FROM INDONESIA - Muhammad Awaluddin; Siti Amalia; Rachmad Budi Suharto (Jurnal Sosioteknologi, 2022)
The world is constantly moving and working in order to revive the hope of improving welfare and quality of life. People’s enthusiasm for the sophistication of IT is no doubt. From this study, our highest determination is to explore how the role of economic globalization as a constructive effort to increase internet users and attract the attention of mobile phone customersin Indonesia. The analysis technique supported by multiple linear regression through three patterns including linear, semi-log (natural logarithm), and double-log (Cobb-Douglas) functions, then extra software applied with Sobel test. We collected data from The Global Economy for the period 2013-2020. We concluded that there is a direct and indirect relationship regarding objectives, hypothetical frameworks, and conceptual models. It is proven, if there is no variable that has a significant effect, because p> 0.10. From the indirect path, economic globalization also does not have a significant effect on mobile phone customers via internet users (p> 0.10). This study recommends novelties that need to be studied intensively for the sustainability of researchers in the future, where it is necessary to expand indicators outside of this text and add time-lag (long term). Last, concrete policies not only concentrated on the theoretical aspect, but smart actions based on practical outcomes that will help the government, academics, and practitioners towards all the dynamics of industry 4.0.